Asset Sales, Investment Opportunities, and the Use of Proceeds - BATES, THOMAS W. (Journal of Finance, 2005)
ABSTRACT This study examines the allocation of cash proceeds following 400 subsidiary sales between 1990 and 1998. Retention probabilities are increasing in the divesting firm's contemporaneous growth opportunities and expected investment. Retaining firms, however, also systematically overinvest relative to an industry benchmark. Shareholder returns to retention decisions are positively correlated with growth opportunities and benchmarked investment, but negatively correlated with benchmarked investment for firms with poor growth opportunities. Shareholder returns to debt distributions are increasing in industry‐benchmarked leverage. Overall, the results of this study cohere with the hypothesized trade‐off between the investment efficiencies associated with retained proceeds and the agency costs of managerial discretion and debt.